Pharmacokinetic Study of Safrole and Methyl Eugenol after Oral Administration of the Essential Oil Extracts of Asarum in Rats by GC-MS - Fan, Yuqi (Biomed Res Int, 2021)
Asarum is a traditional medicine and has been widely used as remedies for inflammatory diseases, toothache, headache, local anesthesia, and aphthous stomatitis in China, Japan, and Korea. Our previous research found that safrole and methyl eugenol were vital compounds that contribute to distinguish the different species and raw Asarum and its processed products apart. The pharmacokinetics of safrole and methyl eugenol after oral administration of Asarum extract has not been reported yet. In this study, a rapid and simple gas chromatography–mass spectroscopy (GC–MS) method that has a complete run time of only 4.5 min was developed and validated for the simultaneous determination and pharmacokinetic study of safrole and methyl eugenol in rat plasma after administration of Asarum extracts. The chromatographic separation was realized on a DB-17 column (30 m × 0.25 mm × 0.25 μm). And detection was carried out under selected ion monitoring (SIM) mode. Plasma samples were pretreated by n-hexane. The pharmacokinetic parameters provided by this study will be beneficial for further developments and clinical applications of Asarum.